Development technology of starter cultures using lactic acid bacteria isolated from fermented Camel milk with cholesterol lowering ability - Bayinjirigala, Sarengaole; Chuluunbat, Tsend-Ayush; Bayin, Jirigala; Menghe, Bilige (Mongolian Journal of Chemistry, 2022)
The aim of the study is to develop a technology of starter cultures for fermented milk using new strains of lactic acid bacteria isolated from Mongolian traditional fermented camel milk. “Khoormog” samples are collected from Inner Mongolia, China. Totally 230 Lactobacillus strains are isolated and screened by acid-, bile- tolerance, lactose decomposition and acid production ability. The cholesterol lowering abilities and adhesiveness on Caco-2 are evaluated. The top 2 strains are identified as Lactobacillus plantarum. These 2 strains are prepared as the starter cultures in milk fermentation. The development technology of starter cultures is studied.